Oral comprehension in middle school 1st year classes and the use of general public videos from the Youtube sharing site - BENAHMED, Ilhem; HADJEM, Kheira Achwak (Journal of Human Sciences, 2024)
In this contribution, we look at how the use of digital media in particular general public videos from the Youtube sharing site develop the oral comprehension of learners in the first year of middle school. More specifically, we are looking at the contribution of the pedagogical design of these videos to oral comprehension. To do this, a comparison was made between sessions without video the methodology adopted; an observation grid and a group interview (post experience) were used to collect the date. A mixed analysis was adopted to verify this.